Composted Sewage Sludge Application Reduces Mineral Fertilization Requirements and Improves Soil Fertility in Sugarcane Seedling Nurseries - Silva, Rafael Dos Santos [UNESP]; Jalal, Arshad [UNESP]; Nascimento, Raimunda Eliane Nascimento Do [UNESP]; Elias, Nathércia Castro [UNESP]; Kawakami, Karen Cossi [UNESP]; Abreu-Junior, Cassio Hamilton; Oliveira, Fernando Carvalho; Jani, Arun Dilipkumar; He, Zhenli; Zhao, Fengliang; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Rossetto, Raffaela; et al. (MDPI, 2022)
Sugarcane demands large amounts of nutrients to reach a high level of productivity. Nutrients are generally supplied by mineral fertilizers, but their high costs and negative environmental impacts have generated interest in greater use of organic nutrient sources such as composted sewage sludge (CSS). In this study, we evaluated changes in soil chemical properties after the application of CSS or CSS/mineral fertilizer (MF) combinations to soil containing sugarcane seedlings under nursery conditions. Treatments included: T1: conventional mineral fertilization (MF) without application of CSS, T2: 100% of the recommended MF (06–30–24); T3: application of 2.5 Mg−1 CSS; T4: 5.0 Mg−1 CSS, T5: 7.5 Mg−1 CSS, T6: 2.5 Mg−1 CSS and 50% MF, T7: 5.0 Mg−1 CSS and 50% MF, T8: 7.5 Mg−1 CSS and 50% MF, T9: 2.5 Mg−1 CSS and 100% MF, T10: 5.0 Mg−1 CSS and 100% MF, T11: 7.5 Mg−1 CSS and 100% MF. Soil chemical properties were evaluated from the soil surface (0.0–0.25 m) and subsurface (0.25–0.50 m) horizons. The results showed that the increase in CSS application did not affect soil organic matter content at either depth, while Zn concentrations increased in the soil subsurface horizon. The application of CSS at 5.0 Mg ha−1 with or without 50% MF resulted in the highest pH values, sum of bases, cation-exchange capacity, P, K, Ca, Mg, Cu, and Zn in surface horizons. The use of CSS as an organic fertilizer in sugarcane nurseries improves soil fertility, reduces mineral fertilizer requirements, and, thus, facilitates the sustainable disposal of sewage sludge.
Keywords: environmental sustainability; organic fertilizer; Saccharum spp; soil quality; urban waste